An investigation into the particle volume scattering function variability in a cascading reservoir system - Alcantara, Enner [UNESP]; Rodrigues, Thanan [UNESP]; Watanabe, Fernanda [UNESP]; Bernardo, Nariane [UNESP] (Springer, 2016)
This work analyzed the spectral and spatial distribution of the particle volume scattering function, beta(p), in a cascading reservoir system. During fieldworks water quality parameters and scattering data were sampled in a predetermined stations. The beta(p) rip was estimated using the ECO-BB9 equipment that measures the volume scattering function, beta, at 117 degrees [beta(117 degrees)]. The estimated beta(p)(117 degrees) were compared with the remote sensing reflectance, Rrs, and the chlorophyll-a (Chl-a) concentration, total suspended matter (TSM) concentration and the transparency (measured using a Secch disk). The results showed that in a hypertrophic environment the beta(p )is dominated by the phytoplankton scattering and in an oligotrophic water system, the scattering by a suspended matter dominates. The beta(p)(117 degrees) variability from a hypertrophic to an oligotrophic aquatic system affects the remote sensing reflectance (R-rs) spectral shape. Due to this, the parametrization of a unique bio-optical model to estimate the optically active components in the water will be challenging.
Keywords: Hydrologic optics; Inherent optical properties; Tropical inland waters